(untitled) (Research, Society and Development, 2020)
This study aims to know the development and effectiveness of teaching material application for trading accounting using visual basic program in enhancing students’ ability to draft financial statements. The methodology used in this study is research and development using pre-experimental design. There are ten steps in analyzing the teaching material using research and development approach. However, this study only uses six steps including (1) Research and Information Collection, (2) Planning, (3) Develop Preliminary Form of Product, (4) Preliminary Field Testing, (5) Main Product Revision, and (6) Main Field Testing. This study is done in Al-Kautsar High School in Bandar Lampung with 35 students of 12th grade as the sample study. The result found that the teaching material application development for trading accounting using visual basic program had been validated by experts and declared feasible to be used. The effectiveness also can be seen from the difference in students’ pretest and posttest scores which done before and after using the teaching material application. Thus, in summary, the use of teaching material application for trading accounting using visual basic program is able to enhance students’ ability to become better.